Conventional and Molecular Improvement of Maize for Drought Tolerance: Review - Garoma, Belay (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
Maize is an important staple crop for food, feed, bioenergy and industrial products globally. Despite the importance of maize as a principal food crop in developing countries, drought is a major constraint that affects maize production, particularly in Sub-Saharan Africa, where maize is grown under rainfed conditions. Plant breeders have been striving to improve and develop drought-tolerant variety. Nevertheless, these efforts still cannot meet the demand for food security due to fast population growth and climatic change. Conventional maize breeding for drought tolerance follows diverse approach includes recurrent selection, backcrossing, pedigree breeding, and subsequently evaluating inbred lines and hybrids at optimum conditions, managed screening site and random stress across multiple environments. Molecular markers were used to select donor parents with drought-adaptive alleles and then integrated into elite maize lines to create a new population of drought-tolerant maize inbred lines and subsequently used to develop hybrids maize tolerance to drought stress.